Analysis of Albert Bandura's Social Learning Theory in Recognizing Students' Interests and Talents - Sri Bintang Abadi; Khoirunnisa Alfadhillah; Putri Salisatu; Tarsono (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine how Albert Bandura's social learning theory can be applied in the context of Islamic Religious Education (PAI) to help teachers identify and develop students' interests and talents. This study uses a qualitative approach with a library research method. The data used in this study consists of primary and secondary sources. Primary sources include Albert Bandura's book